2017
DOI: 10.5483/bmbrep.2017.50.3.190
|View full text |Cite
|
Sign up to set email alerts
|

Neuron-specific expression of p48 Ebp1 during murine brain development and its contribution to CNS axon regeneration

Abstract: P48 Ebp1 is expressed in rapidly proliferating cells such as cancer cells and accelerates cell growth and survival. However, its expression pattern and role in central nervous system development have not been studied. Here, we demonstrated the spatiotemporal expression pattern of p48 Ebp1 during embryonic development and the postnatal period. During embryonic development, p48 Ebp1 was highly expressed in the brain. Expression gradually decreased after birth but was still more abundant than p42 expression after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…Few studies are available that provide in vivo evidence of EBP1 functions due to a lack of an appropriate mammalian model systems. We have previously demonstrated that p48 EBP1 is the major isoform in the developing brain neurons of rats and during murine brain development, whereas there is no detectable p42 EBP1 expression during the embryonic stage 4 , 27 . This also correlated with the ErbB3 expression profile, which is extremely limited in the developing CNS of mice.…”
Section: The Role Of P48 Ebp1 In Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies are available that provide in vivo evidence of EBP1 functions due to a lack of an appropriate mammalian model systems. We have previously demonstrated that p48 EBP1 is the major isoform in the developing brain neurons of rats and during murine brain development, whereas there is no detectable p42 EBP1 expression during the embryonic stage 4 , 27 . This also correlated with the ErbB3 expression profile, which is extremely limited in the developing CNS of mice.…”
Section: The Role Of P48 Ebp1 In Developmentmentioning
confidence: 99%
“…The longer form of p48 Ebp1 is the predominant form that is highly expressed in mammalian cells during embryogenesis and is maintained at a certain level after birth. p42 EBP1 can be detected after birth when the p48 EBP1 level is decreased relative to its level at the embryonic period 4 . In several types of cancer cells, including glioblastoma multiforme (GBM) and lung cancer cells, p48 EBP1 expression was notably high, which was noteworthy because of its oncogenic function.…”
Section: Introductionmentioning
confidence: 99%
“…; Ko et al . ). EBP1 has active involvement of cell growth, apoptosis and differentiation in many cell types (Radomski & Jost ; Xia et al .…”
Section: Introductionmentioning
confidence: 97%
“…EBP1 p48 isoform was found to be predominantly localized in neurons, rather than astrocyte, of the embryonic brain. EBP1 p42 expression was observed in mice after birth [8]. In the injured hippocampus, introduction of p48EBP1 by AAV2 delivery system resulted in notable regeneration of axon growth [8], implying that p48EBP1 may play an important role in processes of neural development and recovery.…”
Section: Introductionmentioning
confidence: 99%
“…EBP1 p42 expression was observed in mice after birth [8]. In the injured hippocampus, introduction of p48EBP1 by AAV2 delivery system resulted in notable regeneration of axon growth [8], implying that p48EBP1 may play an important role in processes of neural development and recovery. However, the physiological function of p48 EBP1 were not defined in developing brain tissues in vivo, because mammalian models of EBP1 deletion have not been developed.…”
Section: Introductionmentioning
confidence: 99%